KONSTRUKSI DAN KLONING PLASMID PCDNA3.1 (+) DENGAN SUBGENOTIP B3 HEPATITIS B CORE ANTIGEN (HBcAg) SEBAGAI KANDIDAT VAKSIN DNA HEPATITIS B - Raudatul Jannah; Lalu Unsunnidhal (Politeknik Medica Farma Husada Mataram, 2019)
Hepatitis B virus (HBV) is a DNA virus that causes hepatitis in humans. DNA vaccines are made by inserting DNA or genes that encode immunogenic proteins into eukaryotic expression vectors. One of the structural genes of HBV that is used as a source of DNA vaccines is the HBcAg gene (HBV / B B3 subgenotype). The purpose of this study was to construct and clone the plasmid pcDNA 3.1 (+) with the HBcAg gene. Confirmation of the SB3-HBcAg gene in the recombinant DNA was carried out by the restriction method and PCR, then confirmation of the base sequence was carried out by the sequencing method. Confirmation data from restriction and PCR obtained were analyzed using a descriptive approach and confirmation data from sequencing were analyzed using ClustalW software. the results showed that the plasmid pcDNA 3.1 (+) with the optimized SB3-HBcAg gene was successfully constructed and cloned.